The dynamics of media- think tank relations: insights from the perspective of Bangladeshi media / Ahmed Khaled Rashid - Rashid, Ahmed Khaled (Faculty of Administrative Science and Policy Studies, 2012)
Media and think tanks have strong incentives to engage with each other. While think tanks require media to propagate their research findings to the policy makers and attentive public, media needs think tanks expertise to explain issues and analyse current affairs, be it foreign policy or macro economy. This study examines the dynamics of interrelation between media and think tanks from the perspective of Bangladeshi media. 57 journalists responded through structured questionnaire and eight senior journalists and think tank communication staff were interviewed as key informants. Findings reveal that independent think tanks are one of the key sources of information for journalists but the usefulness as a source varies depending on thematic areas. Journalists consider research quality as the most critical attribute in a think tank but also believe that research initiatives should be complemented with advocacy activities. Reliability, credibility and extent of research are important considerations for media. Journalists are engaging with think tanks in various forms but they are constantly seeking quickly accessible and usable information. They are less likely to read a policy brief or research report produced by a think tank and more likely to navigate for data or information on the think tanks’ website. Think tanks are often engaging with journalists with a short term focus (e.g. getting media coverage of a dissemination event). Think tanks are far less likely to approach this engagement strategically, developing sustained relations through systematic public relations efforts or including media in capacity development programs. While journalists acknowledge that it may be challenging for think tanks to operate with complete independence in a politically divisive and partisan context, they are more like to engage with think tanks that have a reputation of operating with relative political and operational independence. Findings suggest that think tanks must be more proactive and systematic in reaching out to media, prepare themselves better to present the findings and carefully consider the relevance and timing of research to better engage media.